A Potent Fluorescent Derivative of 8-Hydroxyquinoline Suggests Cell Wall Damage as a Possible Cellular Action of the 5-Triazole 8-Hydroxyquinoline Class - Caroline de Bem Gentz; Marcela Silva Lopes; Priscilla Maciel Quatrin; Mariana Pies Gionbelli; Maycon Antonio de Cesare; Ana Paula Perin; William Lopes; Alexandre Meneghello Fuentefria; Marilene Henning Vainstein; Saulo Fernandes de Andrade (Applied Microbiology, 2025)
Fungal infections are a major but often neglected global health challenge, affecting both human health and agricultural productivity. Current treatments are limited by few drug classes and increasing multidrug resistance, exacerbated by the widespread use of antifungal agents in clinical and agricultural settings. This study investigates the antifungal potential of a novel 8-hydroxyquinoline derivative with a triazole core at the 5-position, synthesized to improve both efficacy and mechanistic understanding as a fluorescent chemical probe. Biological assays demonstrated significant antifungal activity of compound 10 against a range of pathogens, which was active against all Candida species, dermatophytes, and Fusarium solani with MIC values ranging from 0.5 to 4 µg/mL. Confocal fluorescence microscopy of treated fungal cells was conducted and showed a high accumulation of compound 10 at the cell edge. To further investigate the mode of action, results from a sorbitol protection assay suggested a possible cell wall action, and scanning electron microscopy (SEM) revealed cell wall disruption, such as cell shrinkage and surface roughness, in treated fungal cells. These findings highlight the 8-hydroxyquinoline-triazole scaffold as a promising antifungal agent with cell wall damage properties, providing a basis for future therapeutic development against human and plant fungal pathogens.